2003
DOI: 10.1016/s0002-9440(10)63531-6
|View full text |Cite
|
Sign up to set email alerts
|

p53 Haploinsufficiency Profoundly Accelerates the Onset of Tongue Tumors in Mice Lacking the Xeroderma Pigmentosum Group A Gene

Abstract: Mice lacking the xeroderma pigmentosum group A gene (XPA؊/؊ mice), which have a complete deficiency in nucleotide excision repair (NER), are highly predisposed to tongue squamous cell carcinoma (SCC) when exposed to 4-nitroquinoline 1-oxide (4NQO). To explore the effects of the interaction of the NER machinery with p53 in oral tumorigenesis, we generated an XPA؊/؊ mouse strain carrying mutant alleles for p53. This mouse model of 4NQO carcinogenesis demonstrated that despite the same tumor frequency, XPA؊/؊p53؉… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…In a model of mice lacking the xeroderma pigmentosum group A gene (XPA Ϫ/Ϫ mice) and highly predisposed to tongue tumors when exposed to 4-nitroquinoline 1-oxide (4NQO), the p53 haploinsufficiency (TP53Ϫ/ϩ) and complete inactivation (TP53Ϫ/Ϫ) did not increase the incidence of cancer but accelerated dramatically tumor development. 23 In patients with Lynch syndrome, the Proline 72 variant of TP53 accelerates the age at colorectal cancer onset. 14,24 Pro/Pro genotype has also been associated with an earlier age at onset in pharynx, 25 larynx, 25,26 and oral cancer, 25 and in pulmonary cancer in African Americans 27 and Japanese patients.…”
Section: Resultsmentioning
confidence: 99%
“…In a model of mice lacking the xeroderma pigmentosum group A gene (XPA Ϫ/Ϫ mice) and highly predisposed to tongue tumors when exposed to 4-nitroquinoline 1-oxide (4NQO), the p53 haploinsufficiency (TP53Ϫ/ϩ) and complete inactivation (TP53Ϫ/Ϫ) did not increase the incidence of cancer but accelerated dramatically tumor development. 23 In patients with Lynch syndrome, the Proline 72 variant of TP53 accelerates the age at colorectal cancer onset. 14,24 Pro/Pro genotype has also been associated with an earlier age at onset in pharynx, 25 larynx, 25,26 and oral cancer, 25 and in pulmonary cancer in African Americans 27 and Japanese patients.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Rowley et al (27) and Qin et al (28) reported that the p53 gene is an early target for mutation in oral tumor development, with mutations being detected in 40% to 50% of premalignant lesions and SCCs. More recently, Ide et al (29) found that p53 haploinsufficiency profoundly accelerates the onset of tongue tumors in mice lacking the xeroderma pigmentosum group A gene. All together, these results suggest that p53 plays a major and early role in head and neck tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that the histological and molecular changes induced by 4-NQO are similar to those found in human OPLs and OSCCs (2225). The oral carcinogenesis process can be further accelerated by using mice with increased susceptibility to carcinogens, such as mice deficient for the tumor suppressor gene Trp53 (p53) (26, 27). Indeed, heterozygous p53 knockout mice (p53 +/− ) have been extensively used in chemoprevention studies for several carcinogen-induced malignancies (28).…”
Section: Introductionmentioning
confidence: 99%